Digital economy growth in Singapore and Thailand following the post-COVID-19 pandemic - Putri, Sylvia Octa; Yahya, Alya Soraya; Attahira, Azzahra; Nabilasari, Lidya Sisda; Tamaela, Valensya (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This research aims to identify the development of the digital economy and its impact on welfare and economic growth in Singapore and Thailand. The two countries allocate a budget for the specific purpose of building a broadband network all over the country. This national broadband network will help bridge the gap digital divide and encourage modern economic development through e-commerce. However, in its application or implementation, there are many differences between the two countries in their achievements. The method used in this study is Qualitative Research Method. It uses the Literature Review Method to understand better the state of digital economy growth in both countries. Based on the comparison of the results, Singapore is far superior in average internet speed. Although high internet speed lags, however, in the field of e-commerce and means of payment electronics, Thailand is much more accessible compared to Singapore.